Clinicopathological characteristics and prognosis of alpha-fetoprotein positive gastric cancer in Chinese patients - Wang, Daguang (Int J Clin Exp Pathol, 2015)
Purpose: This study aimed to review the clinicopathological, histochemical, and prognostic features of Alpha-Fetoprotein (AFP) positive gastric cancer. Patients and methods: Six hundred and fifty one patients with gastric cancer who underwent gastrectomy between January 2009 and December 2012 at The First Hospital of Jilin University were enrolled in the study. Among them, 45 patients were identified as AFP positive gastric cancer. The clinicopathologic characteristics and prognosis of the AFP positive gastric cancer patients were analyzed. Results: Among the 45 AFP positive patients, serum levels of AFP were < 100 µg/L in nine patients. The histological classification of 45 patients was as follows: hepatoid type, 25 (55.6%) cases; fetal gastrointestinal type, 12 (26.7%) cases; yolk sac tumor type, 2 (4.4%) cases; and mixed type, 6 (13.3%) cases. Twenty nine (64.4%) cases were AFP positive by immunohistochemical analysis; we found no significant difference in AFP positivity and histologic type. However, the differences in the number of metastasis lymph nodes, the maximum tumor diameter, pathological stage, vascular invasion and liver metastasis between the AFP positive group and the negative group were significant. At the same T stage, the liver metastasis status of the AFP positive group was higher than that of the negative group. The AFP positive group had a much poorer prognosis than the negative group. Conclusion: AFP positive gastric cancer is associated with aggressive behavior and poorer prognosis compared to that of AFP negative gastric cancer.